#### Question

Solve the following quadratic equations by factorization:

ax^{2} + (4a^{2} - 3b)x - 12ab = 0

#### Solution

We have been given

ax^{2} + (4a^{2} - 3b)x - 12ab = 0

ax^{2} + 4a^{2}x - 3bx - 12ab = 0

ax(x + 4a) - 3b(x + 4a) = 0

(ax - 3b)(x + 4a) = 0

Therefore,

ax - 3b = 0

ax = 3b

`x=(3b)/a`

or

x + 4a = 0

x = -4a

Hence, `x=(3b)/a` or x = -4a

Is there an error in this question or solution?

Solution Solve the Following Quadratic Equations by Factorization: Ax2 + (4a2 - 3b)X - 12ab = 0 Concept: Solutions of Quadratic Equations by Factorization.